The potential of Tatratea on the foreign market - Bajáková, Petra (2025)
The main goal of this thesis is to assess the potential of Tatra tea, a unique Slovak herbal tea-based liqueur on foreign markets. This work will focus on analysing and identifying target markets for this product. In the first chapter, the attention is aimed at motivations of companies to go international. Different types of market entries are analysed and a closer insight on analysis which will be further used is provided. The second chapter of this thesis is devoted to Tatra tea itself. The characteristics not only of the product but of the whole company as well. Additionally, insights on the global spirits market are provided together with the analysis of major global players and competition. The third and last chapter is devoted to further analysis of Tatra tea’s potential on foreign market.